Lactic Acid Bacteria Fundamentals and Practice - Zhang, Heping; Cai, Yimin; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
The book summarizes the latest research and developments in dairy biotechnology and engineering. It provides a strategic approach for readers relating to fundamental research and practical work with lactic acid bacteria. The book covers every aspect from identification, ecology, taxonomy and industrial use. All contributors are experts who have substantial experience in the corresponding research field. The book is intended for researchers in the human, animal, and food sciences related to lactic acid bacteria. Dr. Heping Zhang is a Professor at the Key Laboratory of Dairy Biotechnology and Engineering Ministry of Education, Inner Mongolia Agricultural University, China. Dr. Yimin Cai works in Livestock and Environment Division, Japan International Research Center for Agricultural Sciences（JIRCAS), Japan.
Phylogenesis and Evolution of Lactic Acid Bacteria -- Biodiversity of Lactic Acid Bacteria -- Genomics of Lactic Acid Bacteria -- Proteomics of Lactic Acid Bacteria -- Lactic Acid Bacteria in Health and Disease -- Lactic Acid Bacteria and the Human Gastrointestinal Tract -- Application of Lactic Acid Bacteria for Animal Production -- Traditional Chinese Fermented Dairy Foods.
Keywords: Microbial genetics; Microbial genomics; Medical biochemistry; Biochemical engineering; Food—Biotechnology.; Biochemistry; Nutrition .; Microbial Genetics and Genomics; Medical Biochemistry; Biochemical Engineering; Food Science; Animal Biochemistry; Nutrition